Targeting Splicing Factor SRSF6 for Cancer Therapy - She, Wenting; Shao, Jun; Jia, Rong (Frontiers in Cell and Developmental Biology, 2021)
Aberrant alternative splicing of pre-mRNA is an emerging cancer hallmark. Many cancer-associated genes undergo alternative splicing to produce multiple isoforms with diverse or even antagonistic functions. Oncogenic isoforms are often up-regulated, whereas tumor suppressive isoforms are down-regulated during tumorigenesis. Serine/arginine-rich splicing factor 6 (SRSF6) is an important splicing factor that regulates the alternative splicing of hundreds of target genes, including many cancer-associated genes. The potential roles of SRSF6 in cancers have attracted increasing attentions in the past decade. Accumulated pieces of evidence have shown that SRSF6 is a potential oncogenic gene that promotes oncogenic splicing when overexpressed. Targeting SRSF6 may suppress tumorigenesis. In this review, we describe the gene, mRNA, and protein structure of SRSF6; summarize the current understanding of the expression, functions, and regulatory mechanisms of SRSF6 during tumorigenesis; and discuss the potential application of targeting SRSF6 in cancer treatment.